2017
DOI: 10.1016/j.labeco.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Increased instruction hours and the widening gap in student performance

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
47
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 49 publications
1
47
1
3
Order By: Relevance
“…Raising instructional time -the allocated number of hours per year that students spend in formal classroom settings -is often found to have positive effects on cognitive skills such as maths and language ability (Bellei, 2009;Cortes and Goodman, 2014;Taylor, 2014), as well as standardised maths, reading, and scientific literacy test scores (Andrietti, 2016;Cattaneo et al, 2016;Huebener et al, 2017). 1 Differences in instructional time between countries are also found to account for some of the observed international gaps in student achievement (Lavy, 2015;.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Raising instructional time -the allocated number of hours per year that students spend in formal classroom settings -is often found to have positive effects on cognitive skills such as maths and language ability (Bellei, 2009;Cortes and Goodman, 2014;Taylor, 2014), as well as standardised maths, reading, and scientific literacy test scores (Andrietti, 2016;Cattaneo et al, 2016;Huebener et al, 2017). 1 Differences in instructional time between countries are also found to account for some of the observed international gaps in student achievement (Lavy, 2015;.…”
Section: Introductionmentioning
confidence: 99%
“…This type of behaviour can cover a broad range of actions such as helping, sharing, and other forms of cooperation (Batson and Powell, 2003), and is distinct from altruism in that it is not purely motivated by increasing another individual's welfare, but can be motivated by, for example, empathy, reciprocity, or self-image (Evren and Minardi, 2017). Pro-social behaviour, and in particular volunteering, is linked to various positive outcomes: at the societal level, it can help build social capital through fostering cooperation and trust and through promoting citizenship (Putnam, 2000), and social capital is linked to higher levels of subjective well-being in societies (Helliwell et al, 2011); at the individual level, it is found to nurture important cognitive and non-cognitive skills that can improve individual 1 There is growing evidence that the effect of raising instructional time on student learning and performance is heterogeneous, and in particular, that higher-performing students tend to benefit relatively more (Cattaneo et al, 2016;Huebener et al, 2017). 2 The importance of instructional time for student achievement varies between educational systems, and in particular, between developed and developing countries (Woessmann, 2016), pointing towards potentially important complementarities in educational production, for example, between instructional time and teacher quality or effective classroom management techniques (Rivkin and Schiman, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marcotte, 2007;Sims, 2008;Fitzpatrick et al, 2011;Herrmann & Rockoff, 2012) or increases in the number of instruction hours provided in a given time period (e.g. Taylor, 2014;Cortes et al, 2015;Lavy, 2015;Rivkin & Schiman, 2015;Huebener et al, 2016) tend to improve student performance.Regarding the second strand, there is a large economic literature on the benefits of additional years of schooling (e.g. Card, 1999;Lochner, 2011).…”
mentioning
confidence: 99%
“…This is an important refinement as the first treated cohort graduated under particular conditions: Due to the nature of the reform, the first treatment cohort graduated from school in the same year as the last control cohort. Therefore, students in this cohort might have different performance 1 Other studies evaluate the reform effect on student performance in ninth grade when the reform serves as a quasi-experiment to estimate the effect of increased instruction time (Huebener et al 2016 find small positive average effects, stronger improvements among high-performing students), on non-cognitive skills (Thiel et al 2014; Dahmann & Anger 2014 provide mixed evidence), and on measures of crystalline and fluid intelligence (Dahmann 2015 finds no general effect, but some evidence for improvements among males). For overviews on further recent findings on the G8-reform, see Huebener & Marcus (2015) and .…”
mentioning
confidence: 99%